A critical evaluation of the Danish national ICT strategy - Friis, Christian S. (Economic & Social Studies, 1997)
The Danish government is committed to a national information and communication technology strategy. The strategy is compared to the European Information Society initiative and the US National Information Infrastructure project, and some differences are described. The Danish strategy, while trying to stimulate the development of the information society also sets out to "counterbalance" the market-forces of the information society by (a) providing the public sector with a strong role, and (b) trying to impose democratic values onto the evolving strategy. The experiences to date show that the democratic goals are not easily achieved.
Keywords: Information society; Communication technology; Denmark